Quantification of naphthoquinone mercapturic acids in urine as biomarkers of naphthalene exposure - Klotz, Katrin; Angerer, Juergen (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2016)
Naphthalene shows carcinogenic properties in animal experiments. As the substance is ubiquitary present in the environment and has a possibly high exposure at industrial workplaces, the determination of naphthalene metabolites in humans is of environmental-medical as well as occupational-medical importance. Here, biomarkers of 1,2- and 1,4-naphthoquinone, as possibly carcinogenic metabolites in the naphthalene metabolism, are of outstanding significance. We developed and validated a liquid chromatography-tandem mass-spectrometric (LC-MS/MS) method for the simultaneous determination of the naphthoquinone mercapturic acids of 1,2- and 1,4-naphthoquinone in human urine samples as a sum of naphthoquinone- and dihydroxynaphthalene-mercapturic acid. Except for enzymatic hydrolysis and acidification, no further sample preparation is necessary. For sample clean-up, a column switching procedure is applied. The mercapturic acids are extracted from the urinary matrix on a restricted access material (RAM RP 18) and separated on a reversed phase column (Synergi Polar RP C18). The metabolites were quantified by tandem mass spectrometry using labelled D5-1,4-NQMA as internal standard. The limits of detection are 3?g/l for 1,2-NQMA and 1?g/l for 1,4-NQMA. Intraday- and interday precision for pooled urine (spiked with 10?g/l and 30?g/l of the analytes) ranges from 5.9 to 15.1% for 1,2-NQMA and from 2.0 to 10.8% for 1,4-NQMA. The developed method is suited for the sensitive and specific determination of the mercapturic acids of naphthoquinones in human urine. A good precision and low limits of detection were achieved. Application of those new biomarkers in biomonitoring studies may give deeper insights into the mechanisms of the human naphthalene metabolism.
EVALuna2:9740